Revealing ancient macroH2A features through in vivo analysis in the cricket Gryllus bimaculatus - Emmanuel Gonzalez-Sqalli; Matthieu Caron; Benjamin Loppin (Proceedings of the National Academy of Sciences, 2026)
macroH2A is one of the most atypical histone variants, being three times larger than canonical H2A due to its unique extranucleosomal macrodomain. Once thought to be vertebrate-specific, macroH2A is in fact an evolutionary ancient histone, encoded by two genes in vertebrates and a single gene in other eukaryotes. However, the absence of macroH2A in Drosophila and Caenorhabditis elegans have precluded its functional characterization beyond vertebrates. Here, we report the functional characterization of macroH2A in an invertebrate, enabled through genome editing in the cricket Gryllus bimaculatus . Endogenous tagging of the cricket macroH2A gene revealed a highly dynamic distribution of macroH2A during gametogenesis and a general association with heterochromatin. In embryos, macroH2A shows a remarkable enrichment in differentiating cells, particularly in the nervous system and muscles. Interestingly, complete gene deletion reveals that macroH2A is dispensable for viability but critical for survival after irradiation. We further show that embryos lacking the linker and macrodomain of macroH2A are equally hypersensitive to DNA damage, demonstrating that this nonhistone region safeguards genome integrity beyond vertebrates. Finally, removing the extranucleosomal domain of macroH2A unexpectedly disturbs its chromatin incorporation in a cell-type-specific manner. This study thus reveals deeply conserved features of macroH2A, shared between insects and vertebrates, but also provides insights about the regulation of its chromatin incorporation.